1983
DOI: 10.1073/pnas.80.19.6010
|View full text |Cite
|
Sign up to set email alerts
|

Human lymphocyte production of immunoreactive thyrotropin.

Abstract: Interferon-a inducers were previously shown to cause human lymphocyte production of a corticotropin (ACTH)-like peptide. Thyrotropin (TSH) was not produced under these conditions. In contrast, this report shows that a T-cell mitogen (staphylococcal enterotoxin A), which does not induce the ACTHlike peptide, caused human lymphocyte production of an immunoreactive (ir) TSH. Lymphocyte synthesis of the ir TSH was first detectable at 24 hr, peaked at 48 hr, and thereafter declined. NaDodSO4/polyacrylamide gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…Examples include adrenocorticotropin hormone (24), f3-endorphin (25), vasoactive intestinal polypeptide (26,27), thyrotropin (28), chorionic gonadotropin (29), follicle-stimulating hormone (30), luteinizing hormone (30), growth hormone (31), and finally growth-hormone-releasing hormone (32). In this latter connection, it is tempting to speculate that growth-hormone-releasing hormone and SRIH might have antagonistic paracrine actions on immune cells just as they affect the release of growth hormone from the pituitary gland in an opposing manner.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include adrenocorticotropin hormone (24), f3-endorphin (25), vasoactive intestinal polypeptide (26,27), thyrotropin (28), chorionic gonadotropin (29), follicle-stimulating hormone (30), luteinizing hormone (30), growth hormone (31), and finally growth-hormone-releasing hormone (32). In this latter connection, it is tempting to speculate that growth-hormone-releasing hormone and SRIH might have antagonistic paracrine actions on immune cells just as they affect the release of growth hormone from the pituitary gland in an opposing manner.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Smith and coworkers demonstrated TSH secretion by human peripheral blood leukocytes stimulated with Staphylococcus enterotoxin A. 1 Subsequent work revealed TSH gene expression in activated mouse spleen cells, 2 and secretion of TSH by mouse splenic mononuclear cells, in particular dendritic cells (DCs) and to a lesser extent T cells and B cells. 3 Human peripheral blood leukocytes have been shown to bind TSH in radiolabeled binding studies 4,5 and by flow cytometry using biotin-labeled TSH.…”
Section: Introductionmentioning
confidence: 99%
“…Such biological intersections are particularly evident between many aspects of the immune system and the neuroendocrine system. Thus, a number of classical neuroendocrine hormones are produced by the cells of the human and murine immune systems (Smith and Blalock, 1981;Smith et al, 1983;Stephanou et al, 1990;Hiestand et al, 1986;Hattori et al, 1990;Wang et al, 2003), and receptors for those are widely distributed across many types of hematopoietic cells (Wang et al, 2003;Chabaud and Lissitzky, 1997;Kruger et al, 1989;Coutelier et al, 1990;Hiruma et al, 1990;Bagriacik and Klein, 2000;Wang et al, 1997). The functional significance of those immune-endocrine circuits, though not fully evident, is nonetheless gradually becoming clear.…”
mentioning
confidence: 99%